Implementation of an image guided intensity‐modulated protocol for post‐prostatectomy radiotherapy: Planning data and acute toxicity outcomes. Issue 4 (27th February 2013) - Chua, Benjamin; Min, Myo; Wood, Maree; Edwards, Sarah; Hoffmann, Matthew; Greenham, Stuart; Kovendy, Andrew; McKay, Michael J.; Shakespeare, Thomas P.
Abstract Introduction There is substantial interest in implementation of image‐guided intensity‐modulated radiotherapy (IG‐IMRT) in the post‐prostatectomy setting. We describe our implementation of IG‐IMRT, and examine how often published organ‐at‐risk (OAR) constraints were met. Furthermore, we evaluate the incidence of acute genitourinary and gastrointestinal toxicities when patients were treated according to our protocol. Methods Patients were eligible if they received post‐prostatectomy radiotherapy (PPRT). Planning data were collected prospectively, and toxicity assessments were collected before, during and after treatment. Results Seventy‐five eligible patients received either 64 Gy (19%) or 66 Gy (81%) in a single phase to the prostate bed. Suggested rectal dose‐constraints of V40Gy < 60% and V60Gy < 40% were met in 64 (85%) and 75 (100%) patients, respectively. IMRT‐specific rectal dose‐constraints of V40Gy < 35% and V65Gy < 17% were achieved in 5 (7%) and 57 (76%) of patients. Bladder dose‐constraint (V50Gy < 50%) was met in 58 (77%) patients. Two patients (3%) experienced new grade 3 genitourinary toxicity and one patient (1%) experienced new grade 3 gastroinestinal toxicity. All grade 3 toxicities had improved by 3‐month review. Overall deterioration in urinary and gastrointestinal symptoms occurred in 33 (44%) and 35 (47%) of patients respectively. Conclusions We report on our implementation of PPRT which takes into account nationally adopted guidelines, with a margin reduction supported by use of daily image guidance. Non‐IMRT OAR constraints were met in most cases. IMRT‐specific constraints were less often achieved despite margin reductions, suggesting the need for review of guidelines. Severe toxicity was rare, and most patients did not experience deterioration in urinary or bowel function attributable to radiotherapy.